Basilar Dolichoectasia with Clot Formation and Subarachnoid Haemorrhage. Issue 4 (1st August 2005) - Michel, P.; Lobrinus, A.; Wintermark, M.; Bogousslavsky, J.
Abstract : PATIENT 1 See Fig. 1. A 71-year-old hypertensive man on clopidogrel for a previous heart attack experienced a mild brainstem ischaemic stroke, followed by progressive hearing loss. 17 months later, acute anarthria, deafness, multiple cranial nerve deficits, and bilateral corticospinal signs developed. 24 h after admission, he died suddenly from an acute subarachnoid haemorrhage. PATIENT 2 See Fig. 2. An 82-year-old hypertensive lady, on chronic oral anti-coagulation for recurrent pulmonary emboli, developed over 6 months progressive dysphagia, dysphonia, dizziness, unsteadiness, aspiration pneumonia and weight loss. When she was hospitalized for acute worsening of symptoms, multiple cranial nerve deficits and bilateral ataxic hemiparesis were found. Over 7 days she progressively developed ophthalmoplegia and a locked-in syndrome, followed by subarachnoid haemorrhage and death on day 17 after admission. COMMENT Intracranial dolichoectasia (fusiform aneurysm) occurs mostly in hypertensive, elderly patients. Its frequent multiple occurrence (as in patient 1) and its association with other